Biodegradación de cianuro en aguas y suelos contaminados por la minería de oro (2018)
In this monograph we studied the biodegradation and the consequences of the use of cyanide in soils and waters in the process of gold extraction, since this element changes the physicochemical characteristics of the same. The processes that take place by microorganisms during degradation in waters or soils, oxidation reactions, hydro catalytic, reduction and substitution / transfer and also the aerobic and anaerobic microorganisms present were studied, studying the advantages and disadvantages of carrying out said processes.